Studi Komparatif Minat Baca Siswa Kelas XI dan Siswa Kelas XII di SMA Unggul Negeri 4 Palembang - Atmojo, M. Bimo Jati; Wahidi, Ahmad (Jurnal Tadwin, 2021)
Abstract This study aims to determine how the reading interest of class XI students and class XII students in State Senior High School 4 Palembang. This research uses quantitative methods. The data collection technique is in the form of a questionnaire. Then there are several other data collection techniques to support complete data income through observation, interviews, and documentation. The population in this study was 975 students of State Senior High School 4 Palembang. The sampling technique used was simple random sampling. The data analysis technique used is descriptive. Scale measurement using the Rating Scale. The theory used to determine students' reading interest is the Reading Aspect according to Harris and Sipay. The results of the data analysis used the mean formula and the grand mean formula. Based on the results of the overall data analysis, it is known that the average value is categorized as high and low. The average value obtained from the sub-variable reading interest of students in the school was 2.736, and the sub-variable reading interest of students outside of school was 2.717, as well as students' reading interest that needed to be improved, namely the indicator of reading books from various types of collections (fiction and nonfiction). This indicator scores lower than the other indicators, namely obtaining an average value of 2.46, so this indicator needs to be improved. Keywords: Reading Interest; students; comparative study